Pertumbuhan dan Hasil TanamanBawang Merah (Alliumascalonicum. L)DenganAplikasiPupuk Kalium dariKombinasiPupukKCl dan Abu JanjangKelapaSawitDenganZatPengaturTumbuhAuksin - Puput Dwi Indriyana; Anthony Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
This study aims to determine the effect of the interaction between potassium nutrients from a combination of KCl fertilizer and oil palm kernel ash by giving auxin growth regulators to the growth and yield of shallots, determining the combination of oil palm basket ash and KCl fertilizer as the best source of nutrients. potassium to increase growth and yield of shallots, and determine the best concentration of auxin growth regulators for growth and yield of shallots.This research was conducted in the experimental garden of the Faculty of Agriculture, University of Riau from July to December 2019. In the form of a completely randomized design (RAL) factors with 2 treatments. The first treatment was 3 combinations of KCl fertilizer and palm kernel ash as a source of potassium and the second treatment was 5 concentrations of auxin growth regulators. The 15 treatment combinations obtained were repeated 3 times so that there were 45 experimental plot units. Each experimental plot was planted with 36 plants, of which 5 plants were sample plants.The parameters observed in this study included: plant height (cm); Fresh weight of tubers per hill (g); Tuber diameter (g); Number of tubers per clump (fruit); Tuber weight suitable for consumption per hill (g); Tuber dry weight per hill (g). The data obtained were processed with variance and continued with the Duncan Multiple Range Test (DNMRT) at the 5% level. The results of this study were that there was no interaction between potassium nutrients from the combination of KCl fertilizer and oil palm kernel ash with the addition of auxin growth regulators to the growth and yield of shallots. The nutrient treatment of potassium only affects the height of shallot plants with the best combination of palm ash and KCl fertilizer, 50% KCl fertilizer (22.5 g KCl.plot-1) + 50% AJKS (73.125 g AJKS.plot-1). The treatment of auxin growth regulators (ZPT) affected plant fresh weight, tuber diameter and tuber weight suitable for consumption with the best auxin growth regulator concentration, which was 2000 ppm. Key words:shallot from seeds, potassium fertilizer, auxin ZPT